Quantifying thermal variation around gray infrastructure in urban India - Subramanian, Divya (Frontiers in Water, 2023)
Dense cities in developing nations face rapid urban sprawl. This alters the local ecology and contributes significantly to the local temperature variation. Grey infrastructure (GI) includes vital processes of sewage treatment and wastewater pumping stations. GI is attributed to large greenhouse gas emissions and high energy utilization, contributing to the local urban heat island effect. A knowledge gap exists in assessing GI contribution to the local temperature variation in megacities of developing nations like India. In this study, the Thermal Variance Index (TVI) was derived around a buffer zone for 7 Sewage Treatment Plants (STPs) in Mumbai. Landsat 8 remote sensing imagery was used with summer and winter variation for alternate years from 2014 to 2021. Three STPs set within densely built surroundings showed a cooling profile. Four STPs located among wetlands displayed a heating profile. The surrounding built spaces showed significant influence on the TVI recorded. The STP Cooling Effect (CE) was further quantified by deducing its Cooling Range (CR) and Cooling Intensity (CI). STPs within densely built areas showed higher Cooling Range and Cooling Intensity. Regression analysis models indicated a high positive correlation for the Normalized Difference Built-up Index (NDBI), Landscape Shape Index (LSI), and STP capacity. Normalized Difference Vegetation Index (NDVI), Modified Normalized Difference Water Index (MNDWI), and STP area showed a strong negative correlation.